1983
DOI: 10.1104/pp.71.2.319
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Metabolism of 5′-Methylthioadenosine in Lemna

Abstract: Evidence is presented that Lemma converts 5'-methylthioadenosine (MTA) to methionine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The nature of the divergence suggested that 4-carbon units were entering cystathionine and/or its products via one or more pathways in addition to that catalyzed by cystathionine y-synthase. This suggestion has now been confirmed by the demonstration that in Lemna the 4-carbon moiety of methionine is derived not only from O-phosphohomoserine via transsulfuration, but also from the ribose carbons of ATP via AdoMet and 5'-methylthioadenosine5 (17).…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…The nature of the divergence suggested that 4-carbon units were entering cystathionine and/or its products via one or more pathways in addition to that catalyzed by cystathionine y-synthase. This suggestion has now been confirmed by the demonstration that in Lemna the 4-carbon moiety of methionine is derived not only from O-phosphohomoserine via transsulfuration, but also from the ribose carbons of ATP via AdoMet and 5'-methylthioadenosine5 (17).…”
Section: Methodssupporting
confidence: 54%
“…Two teine--cystathionine--homocysteine--*methionine (15). The recently discovered synthesis of methionine from 5'-methylthioadenosine (17) results in a net synthesis of only the 4-carbon moiety of methionine, while the methyl and sulfur groups of methionine are independently recycled ( 16).…”
mentioning
confidence: 99%
“…Perhaps the largest source of adenine is generated from the catabolism of MTA which is produced during the biosynthesis of polyamines (22), ethylene (1,2) and methionine (9,10). The observation that polyamine levels first increase during meiosis in the anther tissue of Nicotiana and Datura is consistent with an increase in MTA metabolism at the time pollen development aborts in the APRT-deficient mutants (24,28).…”
Section: Uptake and Metabolism Of Adenine Ba And Bar In Mutant Planmentioning
confidence: 74%
“…Quantitatively less important are adenine and formate, formed during methylthio recycling. We have previously shown that adenine is also efficiently converted to adenine nucleotides (15). Conversion of adenine and its nucleoside probably proceeds by established salvage reactions (17).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the end products formed from the remaining flux through transmethylation is currently under investigation. Preliminary studies with radioactive methionine suggest that a substantial portion of this flux is accounted for by the and the aminopropyl moiety of spermidine; the 4-carbon moiety of methionine is regenerated from 4 of the ribose carbons of ATP (15,19). Some plant tissues are unusual in metabolizing methionine predominantly to ethylene (1,3), and in these tissues ethylene biosynthesis is the major source of methylthio recycling (19).…”
Section: Discussionmentioning
confidence: 99%